Pendidikan, Jarak Rumah dan Dukungan Keluarga terhadap Pemanfaatan Posyandu Lansia - Ariyanto Ariyanto; Tina Yuli Fatmawati; Filius Chandra (Universitas Baiturrahim, 2021)
The elderly population is currently increasing. Based on population projection data, it is estimated that in 2017 there are 23.66 million elderly people in Indonesia (9.03%). It is predicted that the number of elderly people in 2020 (27.08 million), 2025 (33.69 million), 2030 (40.95 million) and 2035 (48.19 million). Data obtained from cadres showed that the elderly had low awareness of joining the posyandu for the elderly. one cader said that the majority of the elderly rarely visit the posyandu for the elderly (only 40% are active). This research is a quantitative study with cross sectional design. The research was conducted at the elderly Posyandu in the Puskesmas Paal X Work Area with 36 respondents in December 2019-January 2020. Data were analyzed univariat and bivariat with the Chi Square test. The results showed that there was a relationship between family support and the utilization of the elderly posyandu, there was no relationship between education and distance from the house with the use of the elderly posyandu in the elderly posyandu in the working area of Puskesmas Paal X, Jambi City.